2009
DOI: 10.1016/j.cbpa.2009.04.617
|View full text |Cite
|
Sign up to set email alerts
|

Emerging targets for antidepressant therapies

Abstract: Despite adequate antidepressant monotherapy, the majority of depressed patients do not achieve remission. Even optimal and aggressive therapy leads to a substantial number of patients who show minimal and often only transient improvement. In order to address this substantial problem of treatment-resistant depression, a number of novel targets for antidepressant therapy have emerged as a consequence of major advances in the neurobiology of depression. Three major approaches to uncover novel therapeutic interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 175 publications
(145 reference statements)
0
26
0
1
Order By: Relevance
“…Pharmacological treatments often target biogenic amines, but despite the plethora of commercially available antidepressants, the search for novel therapeutic targets and specific drugs is an ongoing endeavor for several reasons: (1) Most depressed patients are not adequately treated with monotherapy. Placebo-controlled trials show efficacy rates of B30%, and few people achieve total remission of depressive symptoms despite using multiple therapies (Rakofsky et al, 2009). Recent data from the STAR*D trial revealed remission rates of B30% for citalopram monotherapy, and this only increased to B50-70% with the most intensive combination of therapies (Insel and Wang, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological treatments often target biogenic amines, but despite the plethora of commercially available antidepressants, the search for novel therapeutic targets and specific drugs is an ongoing endeavor for several reasons: (1) Most depressed patients are not adequately treated with monotherapy. Placebo-controlled trials show efficacy rates of B30%, and few people achieve total remission of depressive symptoms despite using multiple therapies (Rakofsky et al, 2009). Recent data from the STAR*D trial revealed remission rates of B30% for citalopram monotherapy, and this only increased to B50-70% with the most intensive combination of therapies (Insel and Wang, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This may be important since much (approximately 50%) Hcy is converted to GSH (24), and both GSH and Hcy along with Cys-Gly are known ligands for the NMDA subclass of glutamate receptor (8). This is interesting since several reports indicate that excitatory glutamatergic neurotransmission may play a role in the pathophysiology of depression (25): Disturbances in glutamate metabolism and NMDA receptors have been associated with depression and suicide tendency, and it has been shown that a single intravenous dose of an NMDA receptor antagonist is sufficient to produce sustained relief from depressive symptoms (26). Although Cys-Gly is a significant component in the linear model predicting depression index score, why it exhibits a negative association and what this might mean in terms of the overall neurobiology of depression is unclear.…”
Section: Discussionmentioning
confidence: 96%
“…Prevalanca depresije kao pratećeg poremećaja hroničnih bolesti raste (61). adekvatnom terapijom antidepresivima postiže se poboljšanje kod većine pacijenata (62). Međutim, 20-30% pacijenata obolelih od depresije rezistentno je na standardnu terapiju koja obuhvata antidepresive, psihoterapiju i elektrokonvulziju (63 stimulacija, koja se postiže stereotaksičkim postavljanjem elektroda, pokazala se kao bezbedna i efikasna metoda u lečenju pacijenata sa Parkinsonovom bolešću, esencijalnim tremorom, distonijom, klaster glavoboljama i hroničnim bolnim stanjima (64)(65)(66)(67), kao i u lečenju depresije (68).…”
Section: Kontrola Sistema Zadovoljstva I Motornog Odgovoraunclassified